Virtual adaptation of resident I-PASS training session during COVID-19 - Rouse, Michael; Abebe, Abebe; Naylor, David; Gibson, Cheryl (Kansas Journal of Medicine, 2022)
Introduction. Effective communication during the patient handoff process is critical for ensuring patient safety. At our academic medical center, first-year interns complete hand-off training before starting clinical rotations. The purpose of this study was to evaluate a virtual handoff training for residents as an alternative to in-person sessions due to limitations imposed by COVID-19. Methods. Fifty residents were administered pre/post surveys to gauge the helpfulness of the training for clinical practice, familiarity and confidence in providing a handoff, and whether they would recommend the virtual format for incoming interns. Additionally, faculty rated the virtual form of the handoff activity, made comparisons to in-person sessions, and assessed the helpfulness of the session for residents in clinical practice. Results. Forty-four residents (88%) and 11 faculty (85%) completed surveys. After the training session, residents who received instruction and feedback reported significant improvements in familiarity with the handoff tool and confidence in their handoff abilities (both p< 0.001). Both residents and faculty were satisfied with the virtual format of handoff training. Most faculty felt the virtual platform was comparable to in-person sessions and would recommend ongoing use of the virtual platform when in-person sessions were not possible. Conclusions. Teaching hospitals mandate resident training to include strategies for a uniform handoff method to avoid medical errors. Adaptation to a virtual platform can be a successful instruction strategy, allowing for didactic and interactive sessions with direct faculty observation and feedback.